Review: International Workshop, An Integration of Use-Wear and Residue Analysis for the Identification of the Function of Archaeological Stone Tools - Cristina Lemorini (EXARC, 2012)
The international workshop, titled An integration of use-wear and residues analysis for the identification of the function of archaeological stone tools, took place in Rome between 5-7 March, 2012 at the Sapienza University and at the National Council of Research (CNR). The event, sponsored by the Wenner Gren Foundation (New York) and by the Ministry of the Cultural Heritage, has been organized and directed by C. Lemorini (Sapienza University) and S. Nunziante Cesaro (ISMN- CNR, SMATCH-ITALIA).